Keadilan Konstitusional dalam Penyelesaian Sengketa Ketatanegaraan Analisis Terhadap Putusan Mahkamah Konstitusi - Rosalinda Irvandi Moonti; Sakina Kantu; Roy Marthen Moonti (Politika Progresif : Jurnal Hukum, Politik dan Humaniora, 2024)
Prior to the Third Amendment of the 1945 Constitution implemented in 2001, there were no rules governing how to resolve conflicts about the constitutional authority of state institutions in the context of Indonesian constitutionalism. In addition, there was no entity that had the authority to decide cases related to the constitutional authority of these institutions. After the Third Amendment of the 1945 Constitution, the Constitutional Court began to be used as a tool to resolve disputes related to the constitutional authority of state institutions. In the event of a dispute regarding constitutional authority, the Indonesian constitutional system provides a way to deal with state institutions when interpreting constitutional orders. In the event of such disputes, this type of research falls under the category of normative research. Constitutional disputes should always be based on the constitution as a clear and consistent source of the Constitutional Court, the public and state institutions can better understand the constitutional boundaries that apply. This is important to create a more effective legal system, where all parties, whether the government, society, or other state institutions, can carry out their roles in accordance with agreed constitutional principles. Therefore, constitutional justice upheld by the Constitutional Court does not only apply to certain cases, but also provides a clear direction for the development of state administration in Indonesia.